Genome-Wide Characterization of the Aquaporin Gene Family in Radish and Functional Analysis of RsPIP2-6 Involved in Salt Stress - Yi, Xiaofang; Sun, Xiaochuan; Tian, Rong; Li, Kexin; Ni, Meng; Ying, Jiali; Xu, Liang; Liu, Liwang; Wang, Yan (Frontiers in Plant Science, 2022)
Aquaporins (AQPs) constitute a highly diverse family of channel proteins that transport water and neutral solutes. AQPs play crucial roles in plant development and stress responses. However, the characterization and biological functions of RsAQPs in radish (Raphanus sativus L.) remain elusive. In this study, 61 non-redundant members of AQP-encoding genes were identified from the radish genome database and located on nine chromosomes. Radish AQPs (RsAQPs) were divided into four subfamilies, including 21 plasma membrane intrinsic proteins (PIPs), 19 tonoplast intrinsic proteins (TIPs), 16 NOD-like intrinsic proteins (NIPs), and 5 small basic intrinsic proteins (SIPs), through phylogenetic analysis. All RsAQPs contained highly conserved motifs (motifs 1 and 4) and transmembrane regions, indicating the potential transmembrane transport function of RsAQPs. Tissue- and stage-specific expression patterns of AQP gene analysis based on RNA-seq data revealed that the expression levels of PIPs were generally higher than TIPs, NIPs, and SIPs in radish. In addition, quantitative real-time polymerase chain reaction (qRT-PCR) revealed that seven selected RsPIPs, according to our previous transcriptome data (e.g., RsPIP1-3, 1-6, 2-1, 2-6, 2-10, 2-13, and 2-14), exhibited significant upregulation in roots of salt-tolerant radish genotype. In particular, the transcriptional levels of RsPIP2-6 dramatically increased after 6 h of 150 mM NaCl treatment during the taproot thickening stage. Additionally, overexpression of RsPIP2-6 could enhance salt tolerance by Agrobacterium rhizogenes-mediated transgenic radish hairy roots, which exhibited the mitigatory effects of plant growth reduction, leaf relative water content (RWC) reduction and alleviation of O2– in cells, as shown by nitro blue tetrazolium (NBT) staining, under salt stress. These findings are helpful for deeply dissecting the biological function of RsAQPs on the salt stress response, facilitating practical application and genetic improvement of abiotic stress resistance in radish.